Telemedicine framework using case-based reasoning with evidences. Issue 1 (August 2015) - Sene, A.; Kamsu-Foguem, B.; Rumeau, P.
Highlights Telemedicine framework with structured knowledge to support medical professionals. Enrichment of the case-based reasoning process with evidences and expert opinions. Knowledge engineering using reasoning of ontology modeling and semantic similarity. Flexible collaborative model to provide a participative and extensible environment. Application in oncology to improve the reliability and safety of medical services.